2023
DOI: 10.1101/2023.01.09.23284326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Centering healthcare workers in developing digital health interventions: usability and acceptability of a two-way texting retention intervention in a public HIV clinic in Lilongwe, Malawi

Abstract: Background: New initiates on antiretroviral therapy (ART) are at high risk of treatment discontinuation, putting their health at risk. In low-resource settings, like Malawi, appropriate digital health applications must fit into local connectivity and resource constraints. Target users' perspectives are critical for app usability, buy-in and optimization. We describe the formative stages of the design of a two-way text-based (2wT) system of tailored reminders and adherence messages for new ART initiates and sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…For participants, the 2wT approach was perceived as user-friendly, responses were easy, and both motivational and visit reminders were appreciated [42]. For HCWs, 2wT was highly usable and was perceived to improve their connection with participants, reflecting their needs [55]. Lighthouse HCWs currently maintain the day-to-day operations and management of the 2wT system independently, factors that enhance the likelihood of sustaining the intervention [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For participants, the 2wT approach was perceived as user-friendly, responses were easy, and both motivational and visit reminders were appreciated [42]. For HCWs, 2wT was highly usable and was perceived to improve their connection with participants, reflecting their needs [55]. Lighthouse HCWs currently maintain the day-to-day operations and management of the 2wT system independently, factors that enhance the likelihood of sustaining the intervention [58].…”
Section: Discussionmentioning
confidence: 99%
“…The 2wT approach was developed in accordance with the Principles for Digital Development [53] and based on the open-source Community Health Toolkit (CHT) [54]. 2wT’s easy-to-use CHT-based design resulted from an iterative human-centered design (HCD) process that incorporated feedback from LT clients, HCWs, and retention officers, described previously [55]. In brief, 2wT is a free, proactive, mHealth intervention that combines automated motivation messages with interactive individualized visit reminders ( Fig 2) [42].…”
Section: Retention Interventionsmentioning
confidence: 99%
“…The 2wT is also free, thereby encouraging client feedback. Additionally, the 2wT intervention is also beneficial to the healthcare facility by helping HCWs streamline their workload by reducing unnecessary tracing and automating the generation of defaulter lists, which can lead to improved efficiency and resource allocation within the healthcare system [37].…”
Section: Discussionmentioning
confidence: 99%
“…Web-based messaging, such as 2wT, has been proven to be effective in influencing HIV-related behaviors [ 26 , 27 ]. Furthermore, 2wT has been tested in other contexts in the countries in the African continent, including Zimbabwe [ 16 - 19 ] and Malawi [ 28 , 29 ]. In these contexts, HCWs found that 2wT was highly usable [ 17 , 28 , 29 ], encouraged clients to proactively engage with the healing process [ 17 ], was safe, was inexpensive, and had value [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, 2wT has been tested in other contexts in the countries in the African continent, including Zimbabwe [16][17][18][19] and Malawi [28,29]. In these contexts, HCWs found that 2wT was highly usable [17,28,29], encouraged clients to proactively engage with the healing process [17], was safe, was inexpensive, and had value [28,29]. However, the application of behavior theory can help guide the understanding of usability and acceptability to ensure optimization for each new adaptation or context.…”
Section: Theory Of Change: Technology Acceptance Modelmentioning
confidence: 99%